THE PRACTICALITY OF INTERACTIVE MULTIMEDIA SOFTWARE LECTORA INSPIRE TOWARDS LEARNING THEME 3 OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Mike Oktavia; Yanti Fitria (Universitas Majalengka, 2023)
The use of technology in the classroom today is still uneven because of teachers who prefer to use traditional media, such as the images found in student textbooks, rather than technology-assisted media. This leads to students becoming bored with their lessons, which results in less effective learning. In grade IV of an elementary school. The ADDIE methodology was applied in this research to generate interactive multimedia.Using the following methods: analysis, planning, development, application, and assessment. Response questionnaires, specifically those from students and teachers, are used to collect data. this study seeks to ascertain the usefulness of interactive multimedia development assisted by Lectora Inspire software. The research of the grade IV teachers at SDN 11 Tanjung Barulak's practicality test results showed that 91.66% of them met the requirements for being